MANdatory - why men need (and are needed for) gender equality progress - Van Laar, Colette; Van Rossum, Aster; Kosakowska-Berezecka, Natasza; Bongiorno, Renata; Block, Katharina (Frontiers in Psychology, 2024)
While much progress has been made towards gender equality, diversity and inclusion in the workplace, education and society, recent years have also revealed continuing challenges that slow or halt this progress. To date, the majority of gender equality action has tended to approach gender equality from one side: being focused on the need to remove barriers for girls and women. We argue that this is only half the battle, and that a focus on men is MANdatory, highlighting three key areas: First, we review men’s privileged status as being potentially threatened by progress in gender equality, and the effects of these threats for how men engage in gender-equality progress. Second, we highlight how men themselves are victims of restrictive gender roles, and the consequences of this for men’s physical and mental health, and for their engagement at work and at home. Third, we review the role of men as allies in the fight for gender equality, and on the factors that impede and may aid in increasing men’s involvement. We end with recommendations for work organizations, educational institutions and society at large to reach and involve men as positive agents of social change.